AFTER ALL, WHAT IS STRUCTURAL LITIGATION? GENERAL NOTIONS AND PRELIMINARY THEORETICAL FOUNDATIONS - de Souza Junior, Joaquim Ribeiro (Seven Editora, 2026)
This paper examines the structural process as an instrument capable of closing the historical gap between Brazil’s broad constitutional catalogue of fundamental rights and the country’s material reality. It outlines the evolutionary path of judicial protection, from the retrospective damage-repair model to the prospective paradigm aimed at transforming public or private structures and policies trapped in systematic non-compliance. The study sets out the core notions of structural problem, process and decision, and discusses the Brazilian taxonomy (normative, collective and individual structural proceedings). It also assesses the importance of extrajudicial control, illustrated by the Carrefour settlement, showing that the enforcement of fundamental rights may dispense with the courts. The article concludes that the structural process—grounded in dialogical participation and progressive decision-making—is an indispensable tool for implementing inclusive policies and enhancing the democratic legitimacy of adjudication. DOI: https://doi.org/10.56238/sevened2026.008-046